Bridging the gender gap in atrial fibrillation. (March 2014) - Oza, Nishaki Mehta; Baveja, Swati; Tedrow, Usha
<x xml:space="preserve">Abstract</x> Women have a similar lifetime prevalence of non-valvular atrial fibrillation (NVAF) compared with that of men. Given the significant morbidity and potential mortality associated with NVAF, it is crucial to understand gender differences with NVAF. Women can be more symptomatic than men. Despite a higher baseline stroke risk, they are less likely to be on anticoagulation. Women have a greater risk of thromboembolism and a similar rate of bleeding risk compared with men on anticoagulation. Initial experience suggests that novel oral anticoagulants have similar safety and efficacy profile in men and women. Although women can have more adverse reactions from antiarrhythmic therapies, they are often referred later than men for ablation. As a group, a mitigating factor in ablation referral is that women also have a higher incidence of procedural complications from catheter ablation. This review summarizes the available literature highlighting significant gender-based differences and also highlights areas for research to improve NVAF outcomes in women.